Public Spending and Financial Inclusion and Their Impact on Inclusive Growth In Indonesia: A Spatial Approach - Della Hardyati Prabowo; Ghozali Maski; Dwi Budi Santoso (Trunojoyo University of Madura, 2023)
Inclusive growth results in equal access to the benefits of growth and, by that, reduces disparities. Public spending plays an important role in supporting economic growth and people's welfare. On the other hand, financial inclusion has the ability to expand opportunities to participate in growth. Using data on government spending and financial inclusion in 34 provinces in Indonesia in 2015-2019, this study aims to examine the link between the two towards inclusive growth. As a result, spending on education and financial inclusion, as well as investment and trade openness, can promote inclusive growth. Expanding access to education as a result of public investment in education will boost labor capacity and productivity. Meanwhile, access to more affordable credit will be realized through an inclusive financial system. Conversely, due to health development gaps, health spending has a negative impact on inclusive growth. The spatial error model with queen contiguity spatial weight matrix shows a significant spatial effect on the error term or residual. The implication is that policies for expanding education, health, and digital access as well as increasing investment and financial literacy need to be carried out to ensure people's affordability to economic opportunities by considering regional aspects.